A Comparative Analysis of Berith and the Sacrament of Baptism and How They Contributed to the Inquisition - Yehonatan Elazar-DeMota (Religions, 2021)
In 1391 Spanish Jews were forcibly converted to Catholic Christianity, and Portuguese Jews suffered the same fate in 1497. Jewish law rendered involuntary converts as anusim and voluntary converts as meshumadim. Christians without Jewish ancestry called them by various names, New Christians, alboraique, xuetas, and marranos, to name a few. In the fifteenth century, Catholic clerical authorities debated whether the New Christians were indeed Christians, albeit coerced. Canonic law rendered the sacrament of baptism as irrevocable. As such, any belief or practice not in accordance with Catholic doctrine was tantamount to heresy. Consequently, the Inquisition sought to rid the Church of the “Judaizing heresy.” On the one hand, the Sinaitic covenant (berith) considered anusim as Jews, even though there were Christians. This paper analyzes Jewish law and canonic law on respective religious identities. It includes an examination of rabbinic texts and rabbinic responsa, and an examination of the sacrament of Christian baptism. Both religious traditions fought for the souls of the anusim, characterizing what Victor Turner calls liminality and communitas.